La calidad de vida de los productores de cuy como vínculos productivos para la población con enfoque en el desarrollo local. - Delgado Acurio, César Ricardo (2021)
The main problem on the subject of guinea pig production has always been the markets, the biggest problem for the producer occurs at the time of marketing, for not considering the transportation costs and other aspects that are taken as opportunities for intermediaries to stay with a high percentage of utility, and in this way they harm the producer who is the one who really makes an effort from the upbringing, care and slaughter of the animal; Thus, an analysis of the quality of life of guinea pig producers was carried out as productive links for the population with a focus on local development. In relation to the type of research, a quantitative approach methodology was used and relied on the inductive - deductive method for the analysis of the facts through reasoning, in order to obtain conclusions that range from the general to the particular, that facilitated the elaboration of general conclusions from the particular facts obtained in the field study through observation and surveys, applied under the line of Administration and Economy for Social Development and with the sub-lines of Economic Environment for Businesses and Innovation.